Fiscal Transparency and Procyclical Fiscal Policy - Asger Lau Andersen; Lasse Holbøll Westh Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
This paper examines why fiscal policy is procyclical in developing as well as developed countries. We introduce the concept of fiscal transparency into a model of retrospective voting, in which a political agency problem between voters and politicians generates a procyclical bias in government spending. The introduction of fiscal transparency generates two new predictions: 1) the procyclical bias in fiscal policy arises only in good times; and 2) a higher degree of fiscal transparency reduces the bias in good times. We find solid empirical support for both predictions using data on both OECD countries and a broader set of countries.
Keywords: D72; E32; E62; 330; fiscal transparency; fiscal policy; procyclicality; business cycle; political economy; Konjunktur; Finanzpolitik; Öffentliche Ausgaben; Bias; Wahlverhalten; Theorie; Entwicklungsländer; Industriestaaten